Protective Effects of Aqueous Extract of Solanum nigrum Linn. Leaves in Rat Models of Oral Mucositis. (20th November 2014) - Patel, Alkesh; Biswas, Subhankar; Shoja, Muhammed Haneefa; Ramalingayya, Grandhi Venkata; Nandakumar, K.
Abstract : Oral mucositis is one of the most debilitating side effects in patient undergoing chemotherapy or chemoradiotherapy. Leaves of the plant Solanum nigrum are used in folklore medicine to treat oral ulcers in India. However, no pharmacological investigation has been carried out till date. Aqueous extract of Solanum nigrum leaves (AESN) was prepared and subjected to various phytochemical screening. HPLC analysis of the ethyl acetate fraction was carried out. The aqueous extract (100 and 200 mg/kg) was further evaluated for its protective effect on two rat models: (a) busulfan plus infrared radiation (chemoradiotherapy) induced oral mucositis and (b) methotrexate (chemotherapy) induced oral mucositis. Various parameters including body weight change, food intake, and mortality were measured. AESN showed protective effect in both models of oral mucositis; however, the higher dose was more effective in chemotherapy induced oral mucositis. A reduction in oral mucositis score ( P < 0.05 ) was observed in the treatment groups. Significant ( P < 0.05 ) improvement in food intake was also observed in AESN treated groups. Aqueous extract of Solanum nigrum leaves has protective effect on chemotherapy and chemoradiotherapy induced oral mucositis in rats.